IZ264 -Tune Up, Zugló! Special Mention - Glorialanza, Alessandra; Saracino, Eliana; Artioli, Orsola; Scillieri, Francesco; Olita, Enrica; Guerrieri, Antonio (4D Journal of Landscape Architecture and Garden Art, 2013)
The Zugló district is an urban area of particular interest for its potential. Although consolidated area within the city, it presents a large territory in transformation: areas currently without meaning and significance, spaces invisible and suspended. Through a series of interventions on the creek, some strategic, others more site specific, it will be possible to re-tune the Zugló district, preparing it for future scenarios, redefining its central role as a connector between the parts and making it a fertile territory of urban experimentation. What are we waiting for? TUNE UP, Zugló!
Keywords: Special Mention